"Turn-on" fluorescent sensor-based probing of toxic Hg(II) and Cu(II) with potential intracellular monitoring. (January 2019) - Rasheed, Tahir; Nabeel, Faran; Adeel, Muhammad; Bilal, Muhammad; Iqbal, Hafiz M.N.
Abstract: In this study, the synthesis of a "turn-on" fluorescent sensor 2-(6-bromobenzo[d]thiazol-2-yl)-3′, 6′-bis(diethylamino)spiro[isoindoline-1, 9′-xanthen]-3-one (BTDX), based on rhodamine and 2-amino-6-bromobenzothiazol was carried out. The introduction of different metal cations reveals that the sensor demonstrates highly selective "switch-on" colorimetric response for Hg (II) and Cu(II) in CH3 CN: H2 O (8:2 v/v) system. A substantial heightening of UV-Vis response attributed to the ring opening of xanthene moiety. This ring opening ascribed because of complexation between the analytes (Hg 2+ /Cu 2+ ) and BTDX. Furthermore, the UV-Vis titration study reveals that the lower detection limit for Hg 2+ and Cu 2+ was as low as 4.9 μM and 3.36 μM along with the binding constant of 4.37 × 10 5  mol −1 and 4.6 × 10 5  mol −1, respectively. As a proof of concept, and promising applications in the biological field to detect Hg 2+, the newly developed sensor has proved its cell permeability with low toxicity and can be used for the intracellular monitoring of these toxic agents in HeLa cells. Therefore, the sensor can be regarded as an accurate fluorescent bio-imaging moiety in live HeLa cells via confocal microscopy.